PPM1D Mutations Drive Clonal Hematopoiesis in Response to Cytotoxic Chemotherapy - Hsu, Joanne I.; Dayaram, Tajhal; Tovy, Ayala; De Braekeleer, Etienne; Jeong, Mira; Wang, Feng; Zhang, Jianhua; Heffernan, Timothy P.; Gera, Sonal; Kovacs, Jeffrey J.; Marszalek, Joseph R.; Bristow, Christopher; et al. (Cell stem cell, 2018)
Clonal hematopoiesis (CH), in which stem cell clones dominate blood production, becomes increasingly common with age and can presage malignancy development. The conditions that promote ascendancy of particular clones are unclear. We found that mutations in PPM1D (protein phosphatase Mn2+/Mg2+-dependent 1D), a DNA damage response regulator that is frequently mutated in CH, were present in one-fifth of patients with therapy-related acute myeloid leukemia or myelodysplastic syndrome and strongly correlated with cisplatin exposure. Cell lines with hyperactive PPM1D mutations expand to outcompete normal cells after exposure to cytotoxic DNA damaging agents including cisplatin, and this effect was predominantly mediated by increased resistance to apoptosis. Moreover, heterozygous mutant Ppm1d hematopoietic cells outcompeted their wild-type counterparts in vivo after exposure to cisplatin and doxorubicin, but not during recovery from bone marrow transplantation. These findings establish the clinical relevance of PPM1D mutations in CH and the importance of studying mutation-treatment interactions. [Display omitted] [Display omitted] •PPM1D is mutated in ∼20% of patients with therapy-related AML or MDS•PPM1D mutations are associated with prior exposure to specific DNA-damaging agents•Mutant PPM1D confers a survival advantage after cisplatin-induced stress•PPM1D mutants lack an advantage under bone marrow transplantation stress Cytotoxic chemotherapies put patients at risk for future hematopoietic malignancies. Goodell and colleagues show that PPM1D mutations confer a survival advantage onto hematopoietic clones by rendering them resistant to DNA-damaging agents such as cisplatin. Selective pressures will be specific to different mutations and should be considered in choice of chemotherapy.